2015
DOI: 10.1002/acn3.207
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of MBP in chronic demyelination

Abstract: ObjectivesMisfolding of key disease proteins to an insoluble state is associated with most neurodegenerative conditions, such as prion, Parkinson, and Alzheimer’s diseases. In this work, and by studying animal models of multiple sclerosis, we asked whether this is also the case for myelin basic protein (MBP) in the late and neurodegenerative phases of demyelinating diseases.MethodsTo this effect, we tested whether MBP, an essential myelin component, present prion-like properties in animal models of MS, as is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 63 publications
(80 reference statements)
5
25
0
Order By: Relevance
“…Along these lines, a recent study also suggested that myelin membrane lipid composition may be altered under two models of demyelination. In this work, MBP surface localization to myelinated processes by immunohistochemistry was diminished, while total MBP levels remained unchanged (88). Additionally, a study investigating the role of mammalian target of rapamycin in oligodendrocyte differentiation observed maintenance of normal myelin protein levels despite a significant reduction in the number of maturing oligodendrocytes (89).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Along these lines, a recent study also suggested that myelin membrane lipid composition may be altered under two models of demyelination. In this work, MBP surface localization to myelinated processes by immunohistochemistry was diminished, while total MBP levels remained unchanged (88). Additionally, a study investigating the role of mammalian target of rapamycin in oligodendrocyte differentiation observed maintenance of normal myelin protein levels despite a significant reduction in the number of maturing oligodendrocytes (89).…”
Section: Discussionmentioning
confidence: 69%
“…Thus, our data suggest that PIs inhibit oligodendrocyte maturation through an alternate mechanism. An intriguing possibility is whether PIs disrupt the crucially important myelin-lipid balance, which may result in inappropriate organization of myelin components, as previously reported (87, 88, 92, 93). Because PIs have been shown to cause dyslipidemia in patients and in non-CNS cell types (71, 94, 95), this could contribute to the white matter loss seen in HAND patients (17, 19).…”
Section: Discussionmentioning
confidence: 85%
“…Along these lines, another group showed changes in the protein structure of myelin after cuprizone treatment. Although the amount of myelin basic protein (MBP) in cuprizone‐treated mice was not reduced, the protein aggregated in an insoluble form in the pellet of brain homogenates from cuprizone‐treated mice, which was not observed in control brains or prion‐infected brain . This finding could explain the susceptibility of cuprizone‐treated tissue to detergents (own observations).…”
Section: Discussionmentioning
confidence: 97%
“…In the CNS, myelin basic protein (MBP) found in myelinating oligodendrocytes is indispensable for the formation of myelin sheath [19]. Notable reduction in MBP depicts disruption in myelin stability, causing degradation of myelin sheath and resultant loss [19,20]. Mitochondrial biogenesis is crucial for cell function and its failure can have important implications for the pathogenesis of various neurodegenerative diseases [21]; therefore, we also examined molecular systems associated with mitochondria, notably PGC-1α and COX2 [9].…”
Section: Introductionmentioning
confidence: 99%